Development of an on-machine profile measurement system in ELID grinding for machining aspheric surface with software compensation - Sazedur Rahman, M.; Saleh, Tanveer; Lim, H.S.; Son, S.M.; Rahman, M. (2008)
Efficient manufacture of dimensionally accurate optical surface on hard and brittle materials is a major concern for optoelectronic industry. Electrolytic in process dressing (ELID) grinding is proved as a reliable process to achieve this optical quality nano-surface finish on hard and brittle materials. Besides surface finish it is important to ensure dimensional accuracy by improving profile and form accuracy of the ground aspheric surface. Kinematic factors are commonly considered the reasons for the dimensional inaccuracy in a machined part. Software compensation is a direct and economical method to overcome several kinematic factors and improve the dimensional accuracy. Last, but most important, is the monitoring of achieved surface profile to ensure more accurate profile radius in the finished part. So an on-machine profile measurement system based on coordinate measuring machine (CMM) principle has been developed to check the profile radius of the ground surface. In this study software compensation was applied in ELID grinding of an aspheric surface in order to compensate the wheel wear until the measured surface profile machined on BK7 glass reaches within tolerable limit.